Sosialisasi Peran Jumantik dalam Peningkatan Kesadaran Masyarakat terhadap Kebersihan Lingkungan di Posyandu Mardi Sentosa Sumbersari Metro Selatan - Noormawanti Noormawanti; Iswati Iswati; Muhammad Nur; Annisa Nur Firdausyi; Ismatul Izza Al Iftitah; Reni Wijayanti; Eka Susiani; Endang Rostatik (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Environmental health is one of the important factors in improving public health status, one of which is through the prevention of Dengue Hemorrhagic Fever (DHF) caused by the Aedes aegypti mosquito. This Community Service (PKM) activity aims to increase public knowledge and awareness of the role of Mosquito Larvae Monitoring Officers (Jumantik) in preventing DHF in the environment of Posyandu Mardi Sentosa, Sumbersari, South Metro. The activity was carried out through a participatory approach including an initial survey, planning, socialization, mentoring, and evaluation, involving Posyandu cadres, mothers with toddlers, and surrounding residents. The material delivered covered the role of Jumantik, the 3M Plus movement, and Clean and Healthy Living Behavior (PHBS). The results showed an improvement in participants' understanding of the importance of regular larvae inspection and the implementation of the 3M Plus movement, shown through participants' active involvement in discussions and their ability to re-explain the material presented. The outputs of this activity include a report, documentation, a publication article, and a Jumantik educational leaflet. This activity is expected to be an initial step towards a sustainable culture of clean and healthy living in the Posyandu Mardi Sentosa environment.